Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18311/ijmds/2017/18807
|View full text |Cite
|
Sign up to set email alerts
|

Delamanid and its Role in Drug-Resistant Tuberculosis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The other adverse effects are nausea, vomiting, dizziness, low serum potassium levels, paraesthesia, anxiety and tremor. 19 In the clinical trials on the early bactericidal activity of delamanid, it was observed that there was increased reduction in CFU, observed with 200 mg/day and 300 mg/day doses. Delamanid showed monophasic bactericidal activity, in contrast to rifampicin and isoniazid, which showed biphasic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other adverse effects are nausea, vomiting, dizziness, low serum potassium levels, paraesthesia, anxiety and tremor. 19 In the clinical trials on the early bactericidal activity of delamanid, it was observed that there was increased reduction in CFU, observed with 200 mg/day and 300 mg/day doses. Delamanid showed monophasic bactericidal activity, in contrast to rifampicin and isoniazid, which showed biphasic activity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Pre-clinical and clinical studies have shown that delamanid has high potency, least risk for drug-drug interactions and better tolerability, and post-antibiotic effect against intracellular bacilli, and these advantages of delamanid will be helpful in reducing the treatment time and risk of toxicity in MDR-TB. 19 A phase IIb randomised controlled trial in adults with pulmonary MDR-TB, showed improved rates of sputum culture conversion at 2 months when an OBR was augmented with delamanid, as compared to placebo. An open label extension of this trial found that patients who consumed delamanid for 2-6 months had more positive outcomes (cured or completed treatment) and lower mortality than those who took delamanid for ≤2 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation